Deradicalization of Terrorism Prisoner: Evaluation of The Terrorism Client Guidance Program at the Surakarta Correctional Facility - Samto Hadi Isnanto; Ma'ruf Akbar; Billy Tunas (Program Studi S3 Ilmu Manajemen, 2020)
The radicalism that leads to terrorism is a threat to almost every country in the world, leading many countries to employ a deradicalization program to deradicalize people that have been influenced by terrorist ideology. This research purpose is to evaluate the effectiveness of deradicalization effort conducted through â€œterrorism client guidance program at Surakarta Correctional Facilityâ€. Using the CIPP model of evaluation, data is collected from eighteen terrorism clients and a few structural officials as well as all related documents at Surakarta Correctional Facility. The result of this study found that: (1) Evaluation of context component is worth average, (2) Evaluation of input component is worth poor, (3) Evaluation of process component is worth good, and (4) Evaluation of product component is worth average. Overall, the effectiveness of deradicalization conducted through guidance for terrorism client program at Surakarta Correctional Facility is worth average. Although the total evaluation merit of the terrorist clientâ€™s guidance program is still in the level of average, however, the author suggests that the program should be continued by revising some areas of concern. Keywords: Deradicalization, Evaluation Program, Guidance of Terrorism Client.